Resignifying the Field of Family in Social Work Education: - Marín-Rengifo, Alba Lucía (Prospectiva. Revista de Trabajo Social e Intervención Social, 2026)
This paper is part of the research project: Family training for social workers in programs in the Western Pacific region affiliated with CONETS, 2023. It aims to understand the concept of family in training process for Social Work, which will strengthen teaching, research, and practice processes, resignifying knowledge to improve the training of students in this discipline. To this end, relevant data related to training were analyzed from two lines of reflection: the first, places of knowledge in the family (individual and family, theories and intervention processes, transversality); and the second, tensions between theoretical and theoretical-practical modalities in training. The general conclusion is that family training must take into account the social reality of the context, validate its diversity through interdisciplinary curricula, unravel power mechanisms in family representations, and construct discourses from the relational democratization with ethical and political commitment in professional education training.